1997
DOI: 10.1111/j.1574-6976.1997.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation of groundnut byBradyrhizobium: a simple infection process by crack entry

Abstract: Infection of legumes by rhizobia may occur by immediate intercellular penetration of root cells (crack entry) as an alternative mode to the more elaborate infection through infection threads. The intercellular spreading mode of infection is exemplified through a comprehensive description of root infection by Bradyrhizobium and nodule organogenesis in Arachis hypogaea (groundnut). The role of axillary root hairs and the processes of plant penetration and intercellular spreading, of internalization and intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(16 citation statements)
references
References 182 publications
1
15
0
Order By: Relevance
“…Although it is often mentioned for peanut that the bacteria take advantage of the wounds induced by lateral root emergence and thus use a crack-entry mechanism to penetrate the root cortex (Allen and Allen 1940;Sprent 2000), this has been considered to be inaccurate by Boogerd and van Rossum (1997). The term ''crack-entry'' is probably misleading because rhizobia that enter the root do so in the region of tufted hairs that originate from the epidermis of a lateral root primordium (Boogerd and van Rossum 1997). Chandler (1978) and more recently Uheda et al (2001) have described the infection site as being located between a root hair and an adjoining cell, be it either another epidermal cell or a cortical cell.…”
Section: Other Nodule Typesmentioning
confidence: 99%
“…Although it is often mentioned for peanut that the bacteria take advantage of the wounds induced by lateral root emergence and thus use a crack-entry mechanism to penetrate the root cortex (Allen and Allen 1940;Sprent 2000), this has been considered to be inaccurate by Boogerd and van Rossum (1997). The term ''crack-entry'' is probably misleading because rhizobia that enter the root do so in the region of tufted hairs that originate from the epidermis of a lateral root primordium (Boogerd and van Rossum 1997). Chandler (1978) and more recently Uheda et al (2001) have described the infection site as being located between a root hair and an adjoining cell, be it either another epidermal cell or a cortical cell.…”
Section: Other Nodule Typesmentioning
confidence: 99%
“…In another word, RoH is only present in nodulating peanut while absent in non-nodulating peanut plants [15]. These observations signal a close relationship between RoH and peanut nodulation, though previous reports indicated that peanut root infection by Bradyrhizobia is not through root hair because Bradyrhizobia enter the plant at epidermal ruptures [6].…”
Section: Introductionmentioning
confidence: 80%
“…The bacteria are then entrapped in the pocket, which further form ITs [5] in the epidermal cells. The rhizobia engulfed in the ITs penetrate the root hair through ITs into the cells, which were inductively formed by actively dividing cortical cells below the site of bacterial infection in the epidermis [6]. Finally, rhizobia are released in the root cortical nodule primordium cells to differentiate into bacteroids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations